Skryté kurikulum vo svetle metodologického holizmu a metodologického individualizmu. / Hidden curriculum in the light of methodological holism and methodological individualism. - Lukáš Bomba (Czech Pedagogical Society, 2013)
The article analyses theoretical and methodological problem of hidden curriculum at school. It compares individualistic and holistic approach in connection to research, measurement and analysis of hidden curriculum. The goal of the study is to present the inconsistency in understanding and explaining the concept of hidden curriculum. The inconsistency is grounded in the absence of paradigmatical background. The theories of hidden curriculum are devided into two groups. The first group is grounded in individualistic approach and the second group is grounded in holistic approach. The examples of empirical studies are used as tools to grasp hidden curriculum at school. The study concludes that the deϐinitions and understanding of the concept of hidden curriculum are logical conclusions of methodologicalapproach and empirical investigation of hidden curriculum in research. The methodological approach and empirical investigation reversely constitute the theory of hidden curriculum. The individualistic paradigm grasps hidden curriculum as a an implicit socialization of a child through the actions of individuals in the school. The holistic paradigm understands hidden curriculum as institutionalized nature of ideology or the tool for reproduction of society.